THE LEGAL POWER OF COURT RULINGS AS A MEANS OF CURRENT ACCOUNT WITHDRAWAL - Fitri, Fitri (International Journal of Business, Law, and Education, 2022)
The judicial power system in the rule of law has a crucial role in upholding law and justice. The principles of the rule of law, especially the independence of the judiciary, are regulated in the Constitution of the Republic of Indonesia Year 1945 (UUD 1945). Article 24 of the 1945 Constitution stipulates that the judicial power must be independent from the influence of other powers, so that it can administer justice without executive interference. The Supreme Court and the Constitutional Court are institutions that exercise the highest judicial power in the Indonesian judicial system. This research was taken using the method of deductive logic. This method produces specific conclusions from statements of a general nature. The results of the analysis of the legal force of court decisions and the application of Constitutional Court Decisions are analyzed specifically from laws and regulations and other legal sources to formulate scientifically supported conclusions. Based on the analysis and description in the previous chapters, it can be concluded that court decisions that have acquired legal force still have binding and executory force. Bank DKI is obliged to implement and respect the court decision regarding the disbursement of PD Pasar Jaya's current account for compensation payments to Suhaemi Zakir. In addition, Bank DKI did not violate Article 49 paragraph (2) point b of the Banking Law but instead misinterpreted and applied the article. The Constitutional Court decision that invalidated the phrase "for banks" from Article 49 adds to legal certainty and legal expediency.